MEMBANGUN KEUNGGULAN LAYANAN SERTIFIKASI MELALUI INTEGRASI KAPABILITAS ADAPTIF ORGANISASI DAN KAPASITAS STRATEGIS ASESOR - Suwita Yanti, Ayu; Darsana, I Made (Penerbit Lafadz Jaya, 2026)
This study aims to develop an integrative conceptual model that explains the role of organizational dynamic capabilities and assessors' strategic competencies in improving the quality of certification services in the era of digital transformation. The study uses a systematic literature review approach to synthesize recent studies related to competency, professional certification systems, and digital transformation. The results indicate that certification service quality is a multidimensional construct formed through the interaction of individual competencies, organizational capabilities, and digital transformation. Assessors' strategic competencies, particularly flexibility, reflective capacity, and critical thinking skills, play a crucial role in ensuring the validity and reliability of assessments. Meanwhile, dynamic capabilities enable organizations to continuously adapt to environmental changes, thereby maintaining the relevance and effectiveness of services. Digital transformation serves as an amplifier that increases the efficiency, transparency, and adaptability of the certification process, while strengthening the relationship between individual competencies and organizational capabilities. The integration of these three dimensions produces a conceptual model that provides a comprehensive understanding of certification service quality. This study contributes to expanding the literature by integrating individual, organizational, and technological perspectives and providing a conceptual foundation for the development of a more adaptive and future-oriented certification system.